Specific decorations of 17-hydroxygeranyllinalool diterpene glycosides solve the autotoxicity problem of chemical defense in Nicotiana attenuata. Issue 5 (9th February 2021) - Heiling, Sven; Llorca, Lucas Cortes; Li, Jiancai; Gase, Klaus; Schmidt, Axel; Schäfer, Martin; Schneider, Bernd; Halitschke, Rayko; Gaquerel, Emmanuel; Baldwin, Ian Thomas
Abstract: The native diploid tobacco Nicotiana attenuata produces abundant, potent anti-herbivore defense metabolites known as 17-hydroxygeranyllinalool diterpene glycosides (HGL-DTGs) whose glycosylation and malonylation biosynthetic steps are regulated by jasmonate signaling. To characterize the biosynthetic pathway of HGL-DTGs, we conducted a genome-wide analysis of uridine diphosphate glycosyltransferases (UGTs) and identified 107 family-1 UGT members. The transcript levels of three UGTs were highly correlated with the transcript levels two key HGL-DTG biosynthetic genes: geranylgeranyl diphosphate synthase (Na GGPPS) and geranyllinalool synthase (Na GLS ). NaGLS's role in HGL-DTG biosynthesis was confirmed by virus-induced gene silencing. Silencing the Uridine diphosphate (UDP)-rhamnosyltransferase gene UGT91T1 demonstrated its role in the rhamnosylation of HGL-DTGs. In vitro enzyme assays revealed that UGT74P3 and UGT74P4 use UDP-glucose for the glucosylation of 17-hydroxygeranyllinalool (17-HGL) to lyciumoside I. Plants with stable silencing of UGT74P3 and UGT74P5 were severely developmentally deformed, pointing to a phytotoxic effect of the aglycone. The application of synthetic 17-HGL and silencing of the UGTs in HGL-DTG-free plants confirmed this phytotoxic effect. Feeding assays with tobacco hornworm ( Manduca sexta ) larvae revealed the defensive functions of the glucosylation and rhamnosylation steps in HGL-DTG biosynthesis. Glucosylation of 17-HGL is therefore a critical step that contributes to the resulting metabolites' defensive function and solves the autotoxicity problem of this potent chemical defense. Abstract : Glycosylation reactions eliminate the toxic effects of 17-hydroxygeranyllinalool diterpene glycosides to plants while contributing to the defensive functions of these compounds during herbivore attack. S.H. designed and performed the research, analyzed metabolomics and transcriptome data, annotated the UGTs, screened the transient and stable lines, performed the phytotoxicity, enzymatic, and performance assays, developed the quantitative method for 17-HGL and wrote the article. L.C.L. assisted with the expression data. J.L. performed the enzymatic assay. K.G. designed the constructs for the transiently and stably silenced lines. A.S. assisted with the in vitro enzyme activity assay. M.S. assisted with the development of the quantitative 17-HGL method and analysis of phytohormones and general metabolites. B. S. performed NMR measurements and verified the synthetized 17-HGL mixture. E. G. and I.T.B. designed the research and wrote the article. R.H. wrote the article.